Pre-admission statin use and in-hospital severity of 2009 pandemic influenza A(H1N1) disease. - Stephen J Brett; Puja Myles; Wei Shen Lim; Joanne E Enstone; Barbara Bannister; Malcolm G Semple; Robert C Read; Bruce L Taylor; Jim McMenamin; Karl G Nicholson; Jonathan S Nguyen-Van-Tam; Peter J M Openshaw; et al. (PLoS ONE)
Background Statins are drugs that are used to lower plasma cholesterol levels. Recently, contradictory claims have been made about possible additional effects of statins on progression of a variety of inflammatory disorders, including infections. We therefore examined the clinical course of patients admitted to hospital with 2009 pandemic influenza A(H1N1), who were or weren't taking statins at time of admission. Methods A retrospective case-control study was performed using the United Kingdom Influenza Clinical Information Network (FLU-CIN) database, containing detailed information on 1,520 patients admitted to participating hospitals with confirmed 2009 pandemic influenza A(H1N1) infection between April 2009 and January 2010. We confined our analysis to those aged over 34 years. Univariate analysis was used to calculate unadjusted odds ratios (OR) and 95 percent confidence intervals (95%CI) for factors affecting progression to severe outcome (high dependency or intensive care unit level support) or death (cases); two multivariable logistic regression models were then established for age and sex, and for age, sex, obesity and "indication for statin" (e.g., heart disease or hypercholesterolaemia). Results We found no statistically significant association between pre-admission statin use and severity of outcome after adjustment for age and sex [adjusted OR: 0.81 (95% CI: 0.46-1.38); n = 571]. After adjustment for age, sex, obesity and indication for statin, the association between pre-admission statin use and severe outcome was not statistically significant; point estimates are compatible with a small but clinically significant protective effect of statin use [adjusted OR: 0.72 (95% CI: 0.38-1.33)]. Conclusions In this group of patients hospitalized with pandemic influenza, a significant beneficial effect of pre-admission statin use on the in-hospital course of illness was not identified. Although the database from which these observations are derived represents the largest available suitable UK hospital cohort, a larger study would be needed to confirm whether there is any benefit in this setting.